2021
DOI: 10.1097/prs.0000000000008051
|View full text |Cite
|
Sign up to set email alerts
|

Long Acellular Nerve Allografts Cap Transected Nerve to Arrest Axon Regeneration and Alter Upstream Gene Expression in a Rat Neuroma Model

Abstract: Neuromas may form after any nerve injury whether trauma, traction injury, or a consequence of amputation. Stump-or end-neuromas develop from completely severing an affected nerve, where axon outgrowth from the unrepaired proximal nerve forms a bulbous swelling of axonal sprouts and scar tissue. The incidence of end-neuromas varies by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Animal studies have shown that nerve regeneration across a long (5 cm) allograft is permanently prevented, and dorsal root ganglia gene expression is altered to arrest growth over a period of 5 months. 33 Similarly, senescence increases and nerve regeneration decreases as nerve autograft lengths increase. 34 Therefore, regenerating axons will likely not reach the end of a GON autograft that is ~7 cm in length.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that nerve regeneration across a long (5 cm) allograft is permanently prevented, and dorsal root ganglia gene expression is altered to arrest growth over a period of 5 months. 33 Similarly, senescence increases and nerve regeneration decreases as nerve autograft lengths increase. 34 Therefore, regenerating axons will likely not reach the end of a GON autograft that is ~7 cm in length.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in rat showed that long, decellularized nerve allografts applied to a free nerve ending arrested the formation of neuroma by exhausting the nerve regenerative potential within a length of between 2.5 and 5 cm over the course of 5 weeks and 5 months. 10,11 While this promising approach benefits from both a protective environment and the longitudinal guidance for sprouting axons at the proximal nerve stump following nerve transection, the use of allografts in the clinic is not ideal due to the shortage of high-quality tissue sources, high variability, and costs associated with cadaveric procurement. Furthermore, these approaches require an extensive length of graft to complete the exhaustion of the native nerve regenerative potential.…”
Section: Discussionmentioning
confidence: 99%
“…While the cap devices have shown promising results in preclinical studies, 8,9 they have yet to be widely adopted, as the limited clinical evidence available suggests that nerve capping remains inferior to existing surgical approaches. 7 Recent studies have demonstrated that application of an acellular allograft provides a template for termination of the axonal growth potential within the length of the device 10 ; while this approach has shown promise, the length (i.e., 5 cm) of allograft required to exhaust the regenerative potential of the injured nerve creates the need for a more extensive surgical site. 11 In this exploratory study, we developed and tested a novel nerve cap graft made of decellularized porcine nerve tissue.…”
mentioning
confidence: 99%
“…It is well known that the chances of reinnervation decrease with longer graft length and the cost of a second graft is therefore not warranted in our opinion. 18 When two-stage breast reconstruction with tissue expanders is performed, one must be cognizant of where the allograft is placed to avoid injury during the second-stage exchange procedure. When a radialateral mastectomy incision is used, our preference is to route the allograft inferior to the incision during the first stage of the procedure.…”
Section: Special Considerations In Direct-to-implant and Tissue Tissu...mentioning
confidence: 99%